Living Kidney Donor Phenotype and Likelihood of Postdonation Follow-up. Issue 1 (January 2018) - Reed, Rhiannon D.; Shelton, Brittany A.; MacLennan, Paul A.; Sawinski, Deirdre L.; Locke, Jayme E.
Abstract : Background: The Organ Procurement and Transplantation Network requires that United States transplant centers maintain follow-up with living donors for 2 years postdonation, but lack of donor follow-up is pervasive. Donor characteristics, including younger age, minority race, and lower education, have been associated with incomplete follow-up, but it is unknown whether altruistic donors, having no previous connection to their recipient, differ from traditional donors in their likelihood of follow-up. Methods: Using the Scientific Registry of Transplant Recipients data, we examined all adult living kidney donors from 2005 to 2015 (n = 63 592) classified as altruistic or traditional, and compared likelihood of 6-month medical follow-up using modified Poisson regression. Results: Altruistic donors did not differ from traditional donors in likelihood of follow-up (adjusted relative risk [aRR], 1.02; 95% confidence interval [CI], 0.99-1.06). Among previously identified at-risk subgroups, however, altruistic donors were more likely to have follow-up than their traditional counterparts, including those who were younger (aRR, 1.04; 95% CI, 1.00-1.09), had less than college education (aRR, 1.05; 95% CI, 1.00-1.11), and were unmarried (aRR, 1.08; 95% CI, 1.04-1.12). Having medical follow-up at 6 months was significantly associated with having follow-up at 1 year (aRR, 1.84; 95% CI, 1.75-1.93) and 2 years (aRR, 1.63; 95% CI, 1.56-1.70) postdonation. Conclusions: These data provide additional granularity on living donor phenotypes associated with short-term (6 month) postdonation follow-up, which is important given its association with future likelihood of follow-up. These findings offer the opportunity to tailor and direct educational efforts to increase living donor follow-up, particularly among groups at higher risk of loss to follow-up. Abstract : The Organ Procurement and Transplantation Network requires follow-up with living donors for 2 years postdonation. Medical follow-up at 6 months is seen to be important given its association with future likelihood of follow-up, and provides the opportunity to tailor and direct educational efforts to increase living donor follow-up. Supplemental digital content is available in the text.